Altered Brain Activity in Strabismic Amblyopic Children as Determined by Regional Homogeneity: A Resting-State Functional Magnetic Resonance Imaging Study - Tan, Si-Wen; Cai, Guo-Qian; Li, Qiu-Yu; Guo, Yu; Pan, Yi-Cong; Zhang, Li-Juan; Ge, Qian-Min; Shu, Hui-Ye; Zeng, Xian-Jun; Shao, Yi (Frontiers in Neuroscience, 2022)
Objective: Earlier research has determined that amblyopia or strabismus may cause remarkable brain anatomical and functional variations. Nonetheless, thus far, the spontaneous changes in brain activity in children with strabismus amblyopia (SA) remains unclear. The purpose of this study was to determine the association between abnormal brain activity in children with SA and its behavioral manifestations. Patients and methods: A total of 24 children with SA (10 male and 14 female children) as well as 24 healthy controls (HCs), including 10 male and 14 female children were closely matched in sex and age, and examined using resting-state functional magnetic resonance imaging (fMRI). The regional homogeneity (ReHo) technique was applied to evaluate spontaneous cerebral activity variations in children with SA and HCs, and the characteristics were evaluated using receiver operating characteristic (ROC) curves. Moreover, associations between altered ReHo values in distinct cerebral areas and behavioral manifestations were assessed using correlation analysis. Results: Remarkably increased ReHo values were observed in the right lingual, right superior frontal medial, left superior parietal, right superior parietal, and right inferior parietal gyri of children with SA compared with HCs. In contrast, mean ReHo values in children with SA were lower in the right cerebellum, left superior frontal gyrus, and left putamen nucleus. According to the ROC curve analysis, the application of ReHo is somewhat feasible for the diagnosis of SA. Conclusion: The anomalous spontaneous activity changes in several brain areas that are caused by SA may indicate neuropathologic mechanisms of visual deficits and oculomotor disorders in children with SA.